Ductylity Behavior of Laminated Hollow Section Bamboo Beam-Column Connections with Glue-in-Rod–Bracket System: An Environmentally Friendly Construction Material Solution - Achmad Saiful Arifin; Karyadi Karyadi; Nindyawati Nindyawati; Eka Nurul Qomaliyah; Imam Mustofa (Proceeding of the International Conferences on Engineering Sciences, 2026)
Wood consumption in Indonesia, which is expected to reach more than 64.84 million m³ by 2025, is putting enormous pressure on forests, as evidenced by the reduction in forest area through the clearing of 96,230 hectares of forest in 2023. To reduce dependence on wood as a building material, alternative materials with comparable physical and mechanical properties are needed. Bamboo, especially laminated bamboo, was chosen because it has high tensile strength, a short harvest time, and abundant availability. This study examines the behavior of hollow section laminated bamboo beam-column connections with a glue-in-rod-bracket system to determine the ductility of the connection under unidirectional (static) loads. An experimental method was used with the independent variables of diameter and number of bolts, while the dependent variables included the moment-rotation of the connection, stiffness, strength, and ductility. The results show that the average ductility values for 4 and 6 thread rods D6, D8, and D10 mostly meet the SNI 1729 (≥1.25) and AISC 360 (rotation >0.03 rad) standards, with classifications ranging from "partially ductile" to "fully elastic." However, the 10-diameter 6-thread rod only achieved a ductility of 1.2, thus failing to meet the SNI standard. Based on the Handbook of Structural Steel Connection Design and Details, all connections fall into the non-seismic category because their ductility values are less than 3. These findings confirm the potential of laminated bamboo as an environmentally friendly construction material, while also providing technical guidelines for the design of non-seismic beam-column connections.